Comprehensive guide to neurosurgical conditions - Agrawal, Abhishek; Britz, Gavin (Springer, 2015)
This comprehensive guide answers commonly asked questions about neurosurgical conditions related to brain and spinal cord. Comprehensive Guide to Neurosurgical Conditions fills the gap which arises after a diagnosis is made on the loved one, explaining the basics of neurosurgical diseases and their management. Comprehensive Guide to Neurosurgical Conditions, looks at the Neurosurgical team, the Intensive Care Unit and the basic as well as the emergency neurosurgical procedures in a comprehensive and concise matter. Comprehensive Guide to Neurosurgical Conditions, which is part of a book set including Emergency Approaches to Neurosurgical Conditions, delves into different kinds of brain surgeries, tumors and the management of stroke in chapters written by reputed neurosurgeons worldwide, to help the physicians, the patients and their families cope with all aspects of neurosurgery
Keywords: Nervous system -- Surgery